LAWS GOVERNING JUVENILE JUSTICE IN INDIA: AN IN-DEPTH ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
The juvenile justice system in India is governed by a comprehensive framework thatseeks to protect the rights and welfare of children in conflict with the law. This abstractprovides a concise overview of the key aspects of this legal framework